Evaluating ethics competence in medical education. - Savulescu, J; Crisp, R; Fulford, K; Hope, T (1999)
We critically evaluate the ways in which competence in medical ethics has been evaluated. We report the initial stage in the development of a relevant, reliable and valid instrument to evaluate core critical thinking skills in medical ethics. This instrument can be used to evaluate the impact of medical ethics education programmes and to assess whether medical students have achieved a satisfactory level of performance of core skills and knowledge in medical ethics, within and across institutions.